The influence of sintering temperature on characteristic of ceramics based on bentonite, glass bead and alumina. (March 2019) - Sebayang, P; Simbolon, D H; Zulwita, R R; Pane, J; Simbolon, S; Yunus, M; Kurniawan, C; Setiadi, E A
Abstract: Bentonite, glass bead, and Al2O3 based fine ceramics with variation of sinter temperatures (900, 1000, 1100, and 1200°C) have been prepared by powder metallurgy method. The preparation process of raw materials starts from the mixing of 35 wt% powder bentonite, 35 wt% glass bead, and 30 wt% alumina using High Energy Milling (HEM). After that, the powders are compacted with 80 kgf/cm 2 into pellets. The samples are dried using oven at 100°C for 24 hours. Characterization tested includes physical properties (density, porosity, water absorption, and hardness), microstructure by using SEM and phase analysis by using XRD (X-Ray Diffraction). The results show that the phase formed are the major phase of albite (Al2 NaO8 Si3 ) and quartz (SiO2 ), while the corundum (Al2 O3 ) and nepheline (AlNaO4 Si) are minor phases. The result of analysis shows that bulk density and hardness value tends to increase, while porosity and water absorption tend to decrease along with increasing sinter temperature. The optimum condition was reached at 1100°C with bulk density = 2.43 g/cm 3, porosity = 1.91%, water absorption = 0.8, and hardness = 878.29 HV.